DETERMINAÇÃO DA DENSIDADE DA MADEIRA DE Pinus elliottii ENGELM, ATRAVÉS DE ATENUAÇÃO DE RADIAÇÃO GAMA COMPARADA A MÉTODOS TRADICIONAIS - Palermo, Gilmara Pires De Moura; Latorraca, João Vicente De Figueiredo; Severo, Elias Taylor Durgante [UNESP]; Rezende, Marcos Antônio De [UNESP]; Abreu, Heber Dos Santos (Instituto de Florestas da Universidade Federal Rural do Rio de Janeiro, 2023)
The objective of this research was to evaluate three methods of density determination (12% moisture content and basic density). The methods applied were: Stereometry for immersion, and stereometry for direct measurement and gamma ray. Tree of Pinus elliottii of 8, 15, 25 e 35 age, from reforestation submitted or not drawing resin process, were harvested and then sectioned at the DBH, base, 25%, 50%, 75% and 100% of commercial height. The obtained results showed that the applied methods did not present statistic significant differences. However, the method by gamma ray allowed to determine the density of millimeter by millimeter according to direction pith-bark and to transform the density to 12% of moisture content in basic density and density to 0% of moisture content, without saturation and total drying of sample, respectively.

O objetivo desta pesquisa foi avaliar três métodos de determinação da densidade da madeira a 12 % e densidade básica. Os métodos usados foram: estereometria por imersão e por medição direta e o método de atenuação por radiação gama. Para tal, foram coletados discos de árvores de Pinus elliottii, oriundos de reflorestamento submetidas ou não ao processo de resinagem, com idade de 8, 15, 25 e 35, nas posições da base, DAP, 25%, 50%, 75% e 100% da altura comercial. Os resultados obtidos mostraram que os métodos empregados não apresentaram diferenças estatisticamente significativas. Entretanto, o método de atenuação da radiação gama permitiu determinar a densidade no sentido medulacasca, de milímetro em milímetro e transformar a densidade obtida na umidade de equilíbrio, em torno de 12% em densidade básica e densidade anidra, sem saturação e secagem total da amostra, respectivamente.
DETERMINATION OF WOOD DENSITY OF Pinus elliottii ENGELM BY ATTENUATION OF GAMA RAY COMPARED WITH THE TRADITIONAL METHODS
Keywords: wood density; Pinus elliottii; gama ray; densidade madeira; Pinus elliottii, radiação gama